Chain cleavage of bioinspired bacterial membranes photoinduced by eosin decyl ester - Moreira, Lucas Gontijo; Almeida Junior, Alexandre Mendes; Camacho, Sabrina Alessio [UNESP]; Estevão, Bianca Martins; Oliveira Junior, Osvaldo Novais; Aoki, Pedro Henrique Benites [UNESP] (ACS Publications, 2020)
Photodynamic therapy (PDT) is promising for bacterial inactivation since cellular internalization of photosensitizers (PS) is not crucial for the treatment effectiveness. Photoinduced damage in the lipid envelope may already induce microbial inactivation, which requires PS capable of easily penetrating into the membrane. Herein, we report on the insertion of the PS eosin decyl ester (EosDec) into Langmuir films of 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), 1,2-dioleoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (DOPG), and cardiolipin (CLP) used as mimetic systems of bacterial membranes. Surface pressure isotherms and polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS) indicated that the hydrophobic nature of EosDec favored deeper penetration in all the phospholipid monolayers. The incorporation of EosDec led to monolayer expansion, especially in the anionic DOPG and CLP owing to repulsive electrostatic interactions, and induced disorder in the lipid chains. Light irradiation of DOPE, DOPG, and CLP monolayers containing EosDec increased the rate of material loss to the subphase, which is attributed to cleavage of lipid chains triggered by contact-dependent reactions between excited states of EosDec and lipid unsaturations. The latter is key for membrane permeabilization and efficiency in microbial inactivation.
Keywords: Membranas (Biologia); Agentes fotossensibilizantes; Terapia fotodinâmica; Inativação bacteriana